“Our Mothers’ Arms”: Ethnodrama of Motherhood Reimagined as Post-Colonial Resistance - Clements, Colleen H.; Abdi, Nimo (Art/Research International)

(untitled) (University of Alberta, 2026)
We use collaborative ethnography and ethnodrama to explore our experiences as mothers: a Somali-born Black mother, and U.S.-born white (working-class) mother. We contend that motherhood is a pivotal experience that politicizes those who experience it in significant ways. We seek to reveal the demands of the system of racial capitalism that exploits the labor of women to avoid providing an adequate safety net for its citizens (Calarco, 2024). This demand falls most heavily on mothers of color, immigrant mothers, and working-class mothers. Being activated to political engagement, however, can be towards liberatory ends or in the service of maintaining the violence of the status quo. In this work, we offer an example of finding solidarity within difference for liberatory purposes, intentionally acting against the more oppressive impulse to “protect our own.” We offer these stories to honor the intergenerational wisdom and strength found in “our mothers’ arms.”